Pengaruh Pendekatan Contextual Teaching And Learning terhadap Kemampuan Berpikir Kreatif Siswa Pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas XII di SMK Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Ajaran 2024/2025 - Jeny Florentina br Ginting; Limmarten Simatupang; Dorlan Naibaho; Dame Taruli; Tianggur Napituplu (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The aim of this research is to determine the influence of the Contextual Teaching and Learning approach on students' creative thinking abilities in Christian religious and character education subjects in class XII at SMK Negeri 1 Sipoholon, North Tapanuli Regency for the 2024/2025 academic year. The method used in this research is a quantitative research method with Pre-Experimental One Shot Case Study statistics. The population was all class Data was collected using a 20 item questionnaire. The results of data analysis show that there is an influence of the Contextual Teaching and Learning approach on students' creative thinking abilities in the Christian religious and character education subjects in class XII at SMK Negeri 1 Sipoholon, North Tapanuli Regency for the 2024/2025 academic year. Test analysis requirements, namely tcount = 8.376 > ttable = 2.042. It is known that the tcount value is in the area of ​​rejection of H0 and acceptance of Ha, so H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of the Contextual Teaching and Learning approach on students' creative thinking abilities in Christian religious and character education subjects in class XII at SMK Negeri 1 Sipoholon, North Tapanuli Regency for the 2024/2025 academic year.